Karakteristik Pasien Dewasa yang Terdiagnosis COVID-19 dengan Komorbid Penyakit Kardiovaskular yang Dirawat di RSPAL dr. Ramelan Surabaya Bulan Juni - Agustus 2021 - Lidya Prillyarista Herlambang (Surabaya Biomedical Journal, 2022)
COVID-19 is a disease caused by SARS-CoV-2. This disease quickly developed into a worldwide pandemic. In China, comorbidities are found in a quarter of COVID-19 patients. Cardiovascular comorbidity ranks third most compared to other comorbidities. However, in Indonesia there is no data related to the characteristics of COVID-19 patients with comorbidities and what types of cardiovascular disease are found.The design of this research is descriptive research with quantitative research methods. This research data was obtained by total sampling technique from medical record data. This research was conducted at RSPAL dr. Ramelan Surabaya in June – August 2021 because on that month, Indonesia experienced the highest spike in COVID-19 cases. The results showed that COVID-19 patients with cardiovascular comorbidities disease have positive RT-PCR results and are dominated by leukocytosis, neutrophilia, lymphopenia, high level of D-dimer, and pneumonia bilateral. The cardiovascular disease that become the most common comorbidity is hypertension.